2018
DOI: 10.1016/j.ijnss.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on nurse turnover intention and influencing factors in Jiangsu Province, China

Abstract: Background Nurses' turnover has been a major concern globally, which is strongly influenced by nurses' intent to leave. However, only a few large sample studies on the predictive factors associated with nurses’ turnover intention were conducted in Jiangsu Province. This study mainly aims to examine the level and factors that influence nurses to leave their work in Jiangsu Province of Eastern China. Methods A cross-sectional survey of 1978 nurses was conducted at 48 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 19 publications
6
57
1
2
Order By: Relevance
“…In the event of a PSI, they may fear medical disputes and legal liability, which is frustrating for the nursing students involved and puts their professional ability into question (Jones & Treiber, 2010). If they cannot obtain effective support and psychological comfort, they will inevitably experience a psychological shadow and effects on their professional self‐confidence (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the event of a PSI, they may fear medical disputes and legal liability, which is frustrating for the nursing students involved and puts their professional ability into question (Jones & Treiber, 2010). If they cannot obtain effective support and psychological comfort, they will inevitably experience a psychological shadow and effects on their professional self‐confidence (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies evidenced multiple contributing factors for nurses' turnover intention. Lower professional title, working in the emergency department, and length of time in the workplace were the factors for turnover intention [23,24]. A similar study conducted in Indonesia identified factors as workload, schedule and personal reasons were determinants for turnover intention [24].…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, according to the 2020 annual National Healthcare Retention & RN Staffing Report 2020 (NSI Nursing Solutions Inc, 2020), in the United States of America (USA), the average turnover rate for bedside nurses is 15.9%. In China, 20.2–56.1% nurses consider or plan to abandon nursing work (Jiang et al., 2019; Lee et al., 2017; Liu et al., 2012), while nurse resignation rates have ranged from 0.64–12.71% (Chen, Li, Li, Lyu, & Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%